Description of the previously unknown advertisement calls of Hyalinobatrachium fragile, H. pellucidum, and Vitreorana antisthenesi (Amphibia: Centrolenidae) - Wen, April; Vasquez, Neida; Castroviejo-Fisher, Santiago (Zootaxa, 2012)
We provide for the first time detailed descriptions of the advertisement calls of three species of glassfrogs of the familyCentrolenidae. The call of Hyalinobatrachium pellucidum is a single, high-pitched tonal note, lacking amplitudemodulation, lasting 0.12–0.18 s, and with a dominant frequency of 4863.54–5408.68 Hz. The call of H. fragile is alsocomposed of a single tonal note, lasting 0.12–0.15 s, with a dominant frequency of 3774.78–3931.89 Hz; however, thecall of H. fragile exhibits amplitude modulation that resembles the shape of a Goldfish cracker when visualized as anoscillogram. The call of Vitreorana antisthenesi consists of a single note of modulated pulses that decrease in energy,lasting 0.03–0.05 s, and with a dominant frequency of 5345.44–5484.73 Hz. We compare these three calls to those of congeneric species in a phylogenetic context.